2001
DOI: 10.1902/annals.2001.6.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Periodontitis and Prematurity. Part I: Obstetric Outcome of Prematurity and Growth Restriction

Abstract: Oral Conditions and Pregnancy (OCAP) is a 5-year prospective study of pregnant women designed to determine whether maternal periodontal disease contributes to the risk for prematurity and growth restriction in the presence of traditional obstetric risk factors. Full-mouth periodontal examinations were conducted at enrollment (prior to 26 weeks gestational age) and again within 48 hours postpartum to assess changes in periodontal status during pregnancy. Maternal periodontal disease status at antepartum, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
368
10
58

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(458 citation statements)
references
References 27 publications
22
368
10
58
Order By: Relevance
“…This is consistent with the literature that shows a reduction in SBP from the beginning until half of the pregnancy (24 weeks), and elevation from the second half until term, when pre-gestational levels are reached, whereas DBP remains reduced by 10% until term 15,16 .…”
Section: Situations Compared Between Study Groups Lpe and Lwe Descripsupporting
confidence: 93%
“…This is consistent with the literature that shows a reduction in SBP from the beginning until half of the pregnancy (24 weeks), and elevation from the second half until term, when pre-gestational levels are reached, whereas DBP remains reduced by 10% until term 15,16 .…”
Section: Situations Compared Between Study Groups Lpe and Lwe Descripsupporting
confidence: 93%
“…In a 5-year prospective study titled "Oral Conditions and Pregnancy (OCAP)" Offenbacher et al [11], demonstrated that both antepartum maternal periodontal disease and incidence/progression of periodontal disease based on full mouth periodontal examination are associated with preterm birth and growth restriction. Regarding the potential mechanism behind this relationship is that premature birth and periodontal disease share a common pathological pathway, inflammation [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The current best practices for diagnosing periodontal disease is based on a set of clinical and radiographic evaluations. Some studies investigating this relationship have used PD, BOP, and CAL as an indicators of periodontal disease [11,[18][19][20][21]. Radiographic evaluation was not possible within the hospital setting and in consideration of the patient's comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Offenbacher and his group in 1996 reported a sevenfold increased risk of a mother with periodontal disease delivering a PTLBW baby [15]. This observation was difficult to ignore and since then many studies have been completed but with varying results [16,17].…”
Section: Obsterics Outcomesmentioning
confidence: 99%